2009
DOI: 10.1177/0148558x0902400108
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Ownership Structure and Innovation: Evidence from Taiwan's Electronics Industry

Abstract: The agency problem of listed companies in East Asia is closely related to their typically concentrated ownership structures. Tight control creates an entrenchment problem that allows the controlling owners' self-interested behaviors to go unchallenged internally by the boards of directors or externally by takeover markets. The primary objective of this paper is to explore the association between the ownership and control structure and innovation. The ownership and control structure is measured first as the div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 59 publications
3
67
0
Order By: Relevance
“…These studies have reported contradictory results: Some studies report a positive relationship between family influence and innovation (Gudmundson et al, 2003;Hsu & Chang, 2011;Llach & Nordqvist, 2010) as well as entrepreneurial activities in general (Zahra, 2005;Zahra, Neubaum, & Huse, 2000). Other studies find a negative relationship between family influence and innovation (e.g., Block, 2012;Chen & Hsu, 2009;Chin, Chen, Kleinman, & Lee, 2009;Czarnitzki & Kraft, 2009;Munari, Oriani, & Sobrero, 2010;Muñ oz-Bulló n & Sanchez-Bueno, 2011). The conflicting results might partly be due to the oversimplified measurement of family influence by merely considering potential family influence through ownership and control.…”
Section: Innovation In Family Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have reported contradictory results: Some studies report a positive relationship between family influence and innovation (Gudmundson et al, 2003;Hsu & Chang, 2011;Llach & Nordqvist, 2010) as well as entrepreneurial activities in general (Zahra, 2005;Zahra, Neubaum, & Huse, 2000). Other studies find a negative relationship between family influence and innovation (e.g., Block, 2012;Chen & Hsu, 2009;Chin, Chen, Kleinman, & Lee, 2009;Czarnitzki & Kraft, 2009;Munari, Oriani, & Sobrero, 2010;Muñ oz-Bulló n & Sanchez-Bueno, 2011). The conflicting results might partly be due to the oversimplified measurement of family influence by merely considering potential family influence through ownership and control.…”
Section: Innovation In Family Firmsmentioning
confidence: 99%
“…We currently lack knowledge on how the (family internal) successors' industry-external experience influences the innovation behavior of family firms. It could be very interesting to see if the potential downside of family CEOs for innovation (e.g., Chen & Hsu, 2009;Chin et al, 2009) could be mitigated by industryexternal experience. Following up on this, we suggest an exploration of whether the investigated relationships differ when comparing family and non-family successors as well as when comparing a single successor and succeeding teams (e.g., siblings).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…As Classen et al (2014) point out, these characteristics of innovation may have specific implications for family owned firms (Zellweger 2007;Miller et al 2011) and several studies investigated whether family firms have a higher innovation performance than non-family owned firms. Unfortunately, the results are rather inconclusive, with some studies finding a positive (e.g., Craig and Dibrell 2006;Ayyagari et al 2011), and others a negative relationship between family ownership and innovation performance (e.g., Block et al 2013;Chin et al 2009). Classen et al (2014) show that family SMEs outperform non-family SMEs regarding process innovation outcomes-but not product innovation outcomeswhen controlling for innovation expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic of return on total assets at FB has been driven by return on sales, although the advantage in this margin was diluted during the previous decade to the point of disappearing in 2008, suggesting that their market power to translate differentiation into higher prices is low. This contradiction is not surprising considering the typical portrait of FB, revealing the persistence of important competitive disadvantages in key intangible assets for differentiation (Casillas, Moreno, & Barbero, 2011;Cooper, Upton, & Seaman, 2005;Kontinen & Ojala, 2010;Miller, McLeod, & Oh, 2001;Westhead, 1997), related to the lack of intellectual capital, knowledge (Block et al, 2011;Le Breton-Miller, Miller, & Lester, 2011) and innovation (Block, 2012;Chin, Chen, Kleinman, & Lee, 2009;Chrisman & Patel, 2012), and lower search breadth (Classen, Van Gils, Bammens, & Carree, 2012). As pointed out by Comi and Eppler (2014), family businesses lose their competitiveness as family managers are averse to taking entrepreneurial risks, over-exploiting existing competences and preventing the firm developing dynamic capabilities.…”
Section: Discussionmentioning
confidence: 99%